The Many Facets of Erythropoietin Physiologic and Metabolic Response - Suresh, Sukanya; Rajvanshi, Praveen Kumar; Noguchi, Constance T. (Frontiers in Physiology, 2020)
In mammals, erythropoietin, produced in the kidney, is essential for bone marrow erythropoiesis, and hypoxia induction of erythropoietin production provides for the important erythropoietic response to ischemic stress, such as during blood loss and at high altitude. Erythropoietin acts by binding to its cell surface receptor which is expressed at the highest level on erythroid progenitor cells to promote cell survival, proliferation and differentiation in production of mature red blood cells. In addition to bone marrow erythropoiesis, erythropoietin causes multi-tissue responses associated with erythropoietin receptor expression in non-erythroid cells such neural cells, endothelial cells and skeletal muscle myoblasts. Animal and cell models of ischemic stress have been useful in elucidating the potential benefit of erythropoietin affecting maintenance and repair of several non-hematopoietic organs including brain, heart and skeletal muscle. Metabolic and glucose homeostasis are affected by endogenous erythropoietin and erythropoietin administration affect, in part via erythropoietin receptor expression in white adipose tissue. In diet-induced obese mice, erythropoietin is protective for white adipose tissue inflammation and gives rise to a gender specific response in weight control associated with white fat mass accumulation. Erythropoietin regulation of fat mass is masked in female mice due to estrogen production. Erythropoietin receptor is also expressed in bone marrow stromal cells and erythropoietin administration in mice results in reduced bone independent of the increase in hematocrit. Concomitant reduction in bone marrow adipocytes and bone morphogenic protein suggests that high erythropoietin inhibits adipogenesis and osteogenesis. These multi-tissue responses underscore the pleiotropic potential of the erythropoietin response and may contribute to various physiological manifestations accompanying anemia or ischemic response and pharmacological uses of erythropoietin.